Fast Reversible Phase Change Silicon for Visible Active Photonics. (1st March 2020) - Wang, Letian; Eliceiri, Matthew; Deng, Yang; Rho, Yoonsoo; Shou, Wan; Pan, Heng; Yao, Jie; Grigoropoulos, Costas P.
Abstract: Both amorphous and crystalline silicon are ubiquitous materials for electronics, photonics, and microelectromechanical systems. On‐demand control of Si crystallinity is crucial for device manufacturing and to overcome the limitations of current phase‐change materials (PCM) in active photonics. Fast reversible phase transformation in silicon, however, has never been accomplished due to the notorious challenge of amorphization. It is demonstrated that nanostructured Si can function as a PCM, since it can be reversibly crystallized and amorphized under nanosecond laser irradiation with different pulse energies. Reflection probing on a single nanodisk's phase transformations confirms the distinct mechanisms for crystallization and amorphization. The experimental results show that the relaxation time of undercooled silicon at 950 K is 10 ns. The phase change provides a 20% nonvolatile reflectivity modulation within 100 ns and can be repeated over 400 times. It is shown that such transformations are free of deformation upon solidification. Based on the switchable photonic properties in the visible spectrum, proof‐of‐concept experiments of dielectric color displays and dynamic wavefront control are shown. Therefore, nanostructured silicon is proposed as a chemically stable, deformation free, and complementary metal–oxide‐semiconductor compatible (CMOS) PCM for active photonics at visible wavelengths. Abstract : Nanosecond‐pulsed lasers introduce reversible phase transformation on silicon nanostructures. The transformations provide a 20% nonvolatile reflectivity modulation within 100 ns. Due to a geometry pinning effect, the lifetime can reach 400 cycles without capping. Reflection probing and comprehensive simulation confirms the mechanisms of crystallization and amorphization. Dynamic displays and active visible wavefront controls are demonstrated as applications.